A aprendizagem baseada em projetos como instrumento de formação para o mundo do trabalho na EPTNM - Xavier, Adriane Campos Dinelly (2025)
The present dissertation aimed to investigate how Project-Based Learning (PBL) can contribute to the preparation of students in Secondary Technical and Vocational Education (EPTNM) for the world of work. The research objectives included understanding the socioeconomic reality of the students, identifying their perceptions of the world of work, examining institutional strategies aimed at fostering comprehension of this field, and developing an educational product based on PBL. The research was conducted using a qualitative approach, employing a multimethod strategy in the investigated field. The study was carried out with third-year students of the Integrated Technical High School Program in Mechatronics at the Federal Institute of Education, Science, and Technology of Amazonas (IFAM), Manaus Distrito Industrial Campus (CMDI). Throughout the year 2024, various data collection instruments were applied, including questionnaires, brainstorming sessions, mind maps, and workshops. The data analysis technique used was Bardin’s (2011) content analysis, which enabled the exploration of meanings within communications. The findings indicate that most students come from low income families, with a diversity of characteristics, personalities, and aspirations, perceiving the institution as a means for academic and personal development. The analysis also emphasized that work, as an educational principle, is a central axis in the training offered by EPTNM. Students’ perceptions indicated a multifaceted understanding of the world of work, encompassing dimensions such as personal fulfillment, competitiveness, and precarious conditions. In this context, the results showed that PBL fostered a collaborative and reflective learning environment in which students took active roles in knowledge construction. The creation of practical outputs—such as podcasts, videos, and graphic materials—demonstrated students' engagement and ability to link theoretical content to real-world demands. Furthermore, PBL proved to be an effective instrument in fostering an understanding of the complexities of the labor market. As a result of the research, an educational product was developed: a didactic guide titled “The Project-Based Learning and the World of Work”, offering pedagogical guidance and strategies to support the implementation of PBL in the context of EPTNM.